2022
DOI: 10.48550/arxiv.2202.09669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of voltage magnitude based unbalance metric for low voltage distribution networks

Abstract: Voltage unbalance in distribution networks (DN) is expected to grow with increasing penetration of single-phase distributed generation and single-phase loads such as electric vehicle chargers. Unbalance mitigation will be a significant concern as voltage unbalance leads to increased losses, reduced motor and inverter efficiency, and becomes a limiting factor for DN operation. The true definition of the unbalance metric needs phasor measurements of network voltage and current. However, such phasor measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These indices are evaluated in [17] and more recently in [25], [31]. In our recent work, [32], we have observed that magnitude based imbalance indicators are highly correlated with true imbalance definition based on sequence components for DNs. Next, we describe the magnitude-based indicators introduced in [30] for generating nodal signals for controlling single-phase flexible resources.…”
Section: E Imbalance Component Of Fsamentioning
confidence: 99%
“…These indices are evaluated in [17] and more recently in [25], [31]. In our recent work, [32], we have observed that magnitude based imbalance indicators are highly correlated with true imbalance definition based on sequence components for DNs. Next, we describe the magnitude-based indicators introduced in [30] for generating nodal signals for controlling single-phase flexible resources.…”
Section: E Imbalance Component Of Fsamentioning
confidence: 99%